2014
DOI: 10.1007/s00520-014-2168-5
|View full text |Cite
|
Sign up to set email alerts
|

Hospice shared-care saved medical expenditure and reduced the likelihood of intensive medical utilization among advanced cancer patients in Taiwan—a nationwide survey

Abstract: HSC is associated with significant medical expenditure savings and reduced likelihood of intensive medical utilization. All types of HPC are associated with medical expenditure savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 16 publications
5
28
0
Order By: Relevance
“…Our study demonstrated that hospice care was associated with a significant reduction in the medical costs incurred by patients with terminal cancer. This finding agrees with that of previous studies . Studies from Taiwan have revealed that hospice home care and shared‐care were associated with 19.8% and 13.3% reductions in medical costs, respectively , with most costs saved in the final 3 months of life .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study demonstrated that hospice care was associated with a significant reduction in the medical costs incurred by patients with terminal cancer. This finding agrees with that of previous studies . Studies from Taiwan have revealed that hospice home care and shared‐care were associated with 19.8% and 13.3% reductions in medical costs, respectively , with most costs saved in the final 3 months of life .…”
Section: Discussionsupporting
confidence: 92%
“…This finding agrees with that of previous studies . Studies from Taiwan have revealed that hospice home care and shared‐care were associated with 19.8% and 13.3% reductions in medical costs, respectively , with most costs saved in the final 3 months of life . With the inclusion of all three forms of hospice services, our analysis showed an even more substantial cost reduction of 25.2% in the final month of life.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found the mean health-care expenditure per person of advanced liver cancer patients receiving hospice care to be 12.6 % less than that of those not receiving hospice care in the last month of their life inTaiwan(H group US$2072 vs. non-H group US$2370). In a previous nationwide survey in Taiwan, Lin et al reported that advanced cancer patients who received hospice care had 15.4 % less health-care expenditure per person than those who did not (US$4314 vs. US$5099)[25]. The difference in findings might be related to the fact that our study was limited to liver cancer patients; the percentage of elderly patients was 55.1 %, and the percentage of receiving hospice home care was 2.1 % in their last month of life.…”
mentioning
confidence: 96%
“…3,7 In East Asia, there is relatively little research on advance care planning (ACP) and AD, and studies suggest that both ACP and AD are less common in this setting. 8,9 Taiwan has been a leader in Asia with regards to palliative care 10 and launched the Patient Self-Determination Act in 2015. According to Patient Self-Determination Act, patients can establish AD regarding the EOL care before death.…”
Section: Introductionmentioning
confidence: 99%